Penerapan Teknik Akrostik dalam Pembelajaran Menulis Puisi Pada Siswa Sekolah Dasar - Ratmiati - -; Sunarti - - (el-Ibtidaiy:Journal of Primary Education, 2021)
Thisstudyaims toimprove poetry writing skills with acrostic techniques in elementary school students. This research is descriptive qualitative. This type of research is a class action research (Class Action Research). The research carried out consisted of two cycles, each cycle being carried out three times.TheThe research procedure includes planning, implementing the action, observing and reflecting. The subjects in this study were 34 grade V elementary school students.After carrying out the research in the first cycle 21 of 34 students got a score of 72.35 who got a "low" qualification. After that, the second cycle of research was carried out, 33 students got an average score of 80 in the "High" qualification. Based on the results of the research in the first and second cycles it proves that the application of acrostic techniques in learning to write poetry in fifth grade elementary school students is very appropriate because the application of these techniques can improve student learning outcomes in writing poetry for the better.